Optimization of biodiesel production process for mixed Jatropha curcas-Ceiba pentandra biodiesel using response surface methodology - Dharma S.; Masjuki H.H.; Ong H.C.; Sebayang A.H.; Silitonga A.S.; Kusumo F.; Mahlia T.M.I. (Elsevier Ltd, 2023)
Alternative fuels; Catalysts; Methanol; Optimization; Potassium hydroxide; Surface properties; Bio-diesel blends; Box-Behnken experimental design; Catalyst concentration; Edible vegetable oil; Non-edible oil; Operating parameters; Physicochemical property; Response surface methodology; Biodiesel